Identification of response classes from heavy metal‐tolerant soil microbial communities by highly resolved concentration‐dependent screenings in a microfluidic system. Issue 5 (11th February 2015) - Kürsten, Dana; Möller, Frances; Gross, Gregor Alexander; Lenk, Claudia; Visaveliya, Nikunjkumar; Schüler, Tim; Köhler, Johann Michael
Summary: One of the most important constituents in soil is the microflora, mainly containing bacteria and fungi with high metabolic versatility and very complex intra‐ and interspecific interactions. Co‐occurrence of several micro‐organism species in soil regulates growth or suppression of single species, either by mutual tolerance or by induction of defence mechanisms, which may result in the release of secondary metabolites for growth suppression of coexisting species. Accumulations of heavy metals in soils can further affect the growth of soil microbial communities; this however is strongly dependent on the capability of micro‐organisms to tolerate heavy metals. Until now, there is no fast and reliable method available to study the growth of microbial communities in highly resolved concentration spaces with environmentally relevant toxic substances such as heavy metals and to identify the tolerance thresholds of micro‐organism communities of selected soils. Here, we present a new methodological approach for the assessment of the growth–response behaviour of soil microbial communities in response to increasing heavy metal concentration (copper) using the droplet‐based micro‐segmented flow technique. Therefore, micro‐organism‐containing soil slurries from contact with metal artefacts from archaeological excavations and from the surface of early copper‐mining areas were studied by separate cultivation in segments in the sub‐μL range and growth, and fluorescence was characterized after cultivation by combined micro‐flow‐through photometry and fluorimetry. Highly resolved dose–response data provided copper tolerance thresholds of the soil communities of the different soils. Concentration‐dependent growth patterns of the micro‐organisms in the segments could be observed and allowed to distinguish response groups with characteristic distribution of photometric and fluorimetric measurement values. It is assumed that these response groups are caused by a sample characteristic growth of metal‐tolerant microbial communities with characteristic critical metal concentrations for growth inhibition. The clear transitions between the groups in small concentration intervals are probably due to sharp transitions between growth and no growth of dominant micro‐organism species at the critical metal concentration. The investigations demonstrate the potential of droplet‐based microfluidic techniques for ultra‐miniaturized ecological studies and its suitability for the assessment of tolerance thresholds of soil microbial communities from heavy metal‐contaminated areas.